FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS INFORMASI LAPORAN KEUANGAN PEMERINTAH DAERAH KABUPATEN ACEH BARAT - Lastri, Surna; Yunina, Fitri; Masriani, Masriani (J-ISCAN: Journal of Islamic Accounting Research., 2021)
This study aims to analyse factors that influence financial report quality. Data collection was done using a questionnaire in Regional Financial Management Agency Aceh Barat District. The population was employee at the finance department. The data were analysed using multiple logistic regression. The result shows that employment of financial accounting standards (FAS) and government employee competencies are partially and simultaneously influence the quality of the financial report.